Guidance profession: comparative analysis between Italy and other European countries - Boerchi, Diego; Benini, Simona; Tacconi, Serena (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In today’s era, characterized by rapid change and unpredictability, it is essential to count on effective career guidance services in which competent and recognised professionals operate. The article analyzes the situation in Italy compared to other European countries, highlighting how the lack of a structured training path and precise regulation of the educational and vocational guidance profession contrasts with more structured trends in the rest of Europe. This situation contributes to the low effectiveness and fragmentation of the guidance services offered, often distancing them from European best practices. The paper highlights the importance of recognising educational and vocational guidance as a specific discipline, requiring professionalism in service delivery, research, and intervention design to improve the effectiveness and quality of the support offered to citizens.